"Canada's Postwar Balance of Payments: A Case Study of Remedies for Balance of Payments Disequilibrium" (A Doctoral Dissertation) - Woodley, John R. (Journal of Finance, 1950)
John R. Woodley, "Canada's Postwar Balance of Payments: A Case Study of Remedies for Balance of Payments Disequilibrium" (A Doctoral Dissertation), The Journal of Finance, Vol. 5, No. 3 (Sep., 1950), p. 293